The double-edged sword effect of employee impression management and counterproductive work behavior: From the perspective of self-control resource theory - Ni, Hui; Duan, Jia; Cao, Qinwei (Frontiers in Psychology, 2023)
Why do employees under impression management sometimes have counterproductive work behaviors? Existing studies have focused on comparing the differences in the use of impression management among different individuals, but cannot explain why a well-behaved individual sometimes behaves badly. Based on the theory of self-control resources, we adopts the survey method of job logs and collects the data of 121 employees. The results show that: (1) the use of self-promotion tactics and ingratiation tactics will promote the depletion of self-control resources. (2) The depletion of self-control resources will encourage employees to engage in counterproductive work behaviors. (3) The effect of self-promotion tactic and ingratiation tactic on the depletion of self-control resources was moderated by emotional intelligence. In the case of high emotional intelligence, this effect is attenuated. And vice versa. (4) Under high emotional intelligence and low emotional intelligence, the indirect effects of self-promotion tactic and ingratiation tactic on employees' counterproductive work behaviors are significantly different. Our research breaks through the between-individual perspective and illustrates the double-edged sword effect of self-promotion tactic and ingratiation tactic on employee counterproductive work behavior and its mechanism from the internal perspective, which is highly innovative.